Burial of oscillating rural-urban and oscillating rural-diasporic indigenous Zimbabweans at dilapidated rural homes (matongo): a case study of the genesis of tent huts and kinship funeral expense fund groups in Buhera District, Zimbabwe. Issue 3 (2nd July 2020) - Machoko, Collis Garikai
ABSTRACT: I argue that an increase in the number of oscillating rural-urban (ORU) and oscillating rural-diasporic (ORD) indigenous Zimbabweans' interments at dilapidated homes has resulted in the genesis and upsurge in temporary tent huts in which African Indigenous Religion (AIR) burial and funeral rituals are performed. Research findings conclude that there is an increasing number of ORU and ORD indigenous Zimbabweans who respectively after their deaths in urban centres and in the diaspora have AIR burial rites performed in tent huts at their deceased parents' ruined homes in the rural areas. Research findings also reveal that traditional burial societies died in Zimbabwe due to economic hardships and that necessitated the formation of Kinship Funeral Expenses Fund Groups (KFEFG) in urban centres by the ORU Zimbabweans and Funeral Insurance Policies (FIP) by Zimbabwean diasporians which replaced burial societies. The conclusion is that despite an increasing number of Zimbabweans living, educated and owning houses in urban centres in Zimbabwe and in foreign countries, they still regard their decrepit rural abodes as their spiritual home and a place for their burials when they die.